2017
DOI: 10.4149/km_2017_2_123
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and wear of iron-based hardfacings reinforced with in-situ synthesized TiB2 particles

Abstract: In this study, four hardfacings, reinforced with in-situ synthesized TiB2 particles, were cladded by tungsten inert gas (TIG) welding, applying flux-cored wires with varying Fe-Ti and Fe-B content. Microstructural examination, macrohardness and microhardness measurements and abrasive wear tests were performed. Morphology of TiB2 changed from a small-sized hexagonal and rectangular to a coarse plate-like one with the increasing common proportion of titanium and boron. Accordingly, hardness and wear resistance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Two times more powerful than structural steel the ADI ductile iron classical quality, with other similar mechanical properties, which is primarily related to ductility and toughness. By adding titanium and boron material in the machining process with hard coated tools, it is possible to increase the hardness and abrasion resistance of the tools [25].…”
Section: Introductionmentioning
confidence: 99%
“…Two times more powerful than structural steel the ADI ductile iron classical quality, with other similar mechanical properties, which is primarily related to ductility and toughness. By adding titanium and boron material in the machining process with hard coated tools, it is possible to increase the hardness and abrasion resistance of the tools [25].…”
Section: Introductionmentioning
confidence: 99%
“…The strength of ADI material is up to two times that of the nodular iron of standard quality, with the same value of toughness and ductility [2]. Hardness and wear resistance can be increased by additions of titanium and boron in the hardfacings [4][5][6]. Previous studies have shown that alloying elements such as Cu and Ni influence temperature, initiation time and completion of the austempering reaction, which provides a larger processing window and easy control of the austempering heat treatments [7].…”
Section: Introductionmentioning
confidence: 99%
“…In general, this may be combatted by either solid solution hardening of austenite or by introduction of hard particles to the steel matrix [12]. As a reinforcement, borides [13], carbides [14][15][16][17] and cermets [18][19][20][21] have been studied. Under the present research, obtaining a WC reinforced PTAW hardfacing with an austenitic matrix is attempted, and sliding wear of the obtained hardfacing is studied under room and elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%